Absolute and infinite: on the discrepancies around the problem of the horizon of appearing in Henry and Patočka - Rivera Schneider, Fabián (Anales del Seminario de Historia de la Filosofía, 2022)
In this article we propose to reflect on the discrepancies around the horizon of appearing in phenomenology, starting with Henry and Patočka. In this sense, it is tried to show, on the one hand, how it is that for the French philosopher Life would be the fundamental phenomenon to be studied, Life that would have as an essential character to be absolute, therefore, different from any foundation that folds it to a external horizon that divides that absolute character. For its part, it will seek to show how the Czech thinker understands that the phenomenological procedure should be guided by an asubjective principle, this in the interest of criticizing the subjective guarantor of correlational intentionality. This asubjective tendency would be completed in the attempt to refer appearing to the field of appearing, towards an infinite horizon of appearance, which would not need to be sustained by the immanence of consciousness. In short, an attempt will be made to show how absolute and infinite act respectively as the negation and affirmation of the horizon of appearing in phenomenology.
Keywords: Absolute; Phenomenology; Horizon; Henry; Infinite; Patočka